2018
DOI: 10.1161/jaha.117.008088
|View full text |Cite
|
Sign up to set email alerts
|

Sex and Racial Disparities in Cardiac Rehabilitation Referral at Hospital Discharge and Gaps in Long‐Term Mortality

Abstract: BackgroundCardiac rehabilitation (CR) referral is recommended for eligible patients, regardless of sex or race. It is unclear whether inequality in CR referral practices was associated with patients’ long‐term survival.Methods and ResultsWe linked the American Heart Association Get With The Guidelines Coronary Artery Disease registry with Medicare claims data for 48 993 coronary artery disease patients from 365 hospitals across the United States between 2003 and 2009. We used generalized estimation equations t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
77
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(87 citation statements)
references
References 51 publications
5
77
0
Order By: Relevance
“…These findings are supported by prior studies that women are less likely to utilise secondary preventive care. Although the fact that women are being referred to a cardiac rehabilitation program less often in the first place may contribute to the lower attendance rate compared to men, women were also reported to have greater dropout rates from the programs than men in past studies [12,[20][21][22]. Local and international studies have also found a sex difference in the use of secondary prevention medications [13,23,24].…”
Section: Discussionmentioning
confidence: 99%
“…These findings are supported by prior studies that women are less likely to utilise secondary preventive care. Although the fact that women are being referred to a cardiac rehabilitation program less often in the first place may contribute to the lower attendance rate compared to men, women were also reported to have greater dropout rates from the programs than men in past studies [12,[20][21][22]. Local and international studies have also found a sex difference in the use of secondary prevention medications [13,23,24].…”
Section: Discussionmentioning
confidence: 99%
“… 116 Likewise, they are less likely to be referred for and to receive cardiac rehabilitation 116,117 . One study noted that women and minorities that received cardiac rehabilitation had significantly lower mortality rates than those who did not, yet Black patients were still 20% less likely to be referred to cardiac rehabilitation than White participants 118 . The resultant 7% Black versus White mortality gap could potentially be reduced by equitable cardiac rehabilitation referrals 118 .…”
Section: Methodsmentioning
confidence: 99%
“…One study noted that women and minorities that received cardiac rehabilitation had significantly lower mortality rates than those who did not, yet Black patients were still 20% less likely to be referred to cardiac rehabilitation than White participants 118 . The resultant 7% Black versus White mortality gap could potentially be reduced by equitable cardiac rehabilitation referrals 118 . To date, there have been no reported racial disparities in outcomes of critical care rehabilitation, but it should be noted that critical care rehabilitation is most often the beginning of a long recovery.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies show that 91% of patients in contemporary coronary stent trials were White ( 5 ). Although there is a suggestion that the worse outcomes in Black patients treated with coronary stents is due partially to social determinants of health, which may be outside of the cardiologist’s control ( 6 ), the fact that minority groups are less likely to be treated with effective cardiac medications and to be referred for cardiac rehabilitation at hospital discharge likely plays a role as well ( 7 , 8 ). Patient race appears to play a role in clinician decision-making ( 9 ).…”
Section: Consequences Of a Nondiverse Cardiovascular Workforcementioning
confidence: 99%